Perancangan Website Layanan Servis Dan Informasi Toko Komputer Menggunakan Model Prototype Pada Toko Best Computer - Ujianto, Tabah; Saepul Azis, M.; Verda Saputra, Depryal; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
The development of information technology has encouraged various businesses to utilize websites as a medium for services and information. Best Computer, a store engaged in the sale, repair, and servicing of computer devices, faces challenges in providing information about its services to customers. This study aims to design a service and information website for Best Computer Store as a solution to the problem of limited service information and the status of device repairs, which are still carried out manually. The system was developed using the prototype method to meet the functional needs of the store. In the data collection process, this study involved observation, interviews with stakeholders, and literature review. The system implementation utilized the Laravel framework based on PHP and MySQL database, and system testing was conducted using the Black Box Testing method. The research results indicate that the designed system can improve the efficiency of service information delivery and simplify the process of checking repair status in real-time. Additionally, the system facilitates customer access to product and service information, thereby enhancing the store's operational efficiency in managing the various services provided.